2009
DOI: 10.1590/s1519-69842009000300021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the hydrological regime on the ichthyofauna of riverine environments of the Upper Paraná River floodplain

Abstract: In this work, spatial and temporal variations in the diversity (species richness and Simpson's Diversity Index) and abundance (indexed by the capture per unit effort -CPUE; total and for reproductive groups) of fish from three rivers (Baía, Ivinheima and Paraná) located in a floodplain of the Upper Paraná River basin were analyzed over a period of 20 years . In addition, we evaluated the relationships of these ecological attributes with variations in the hydrologic regime, considering the possible effects of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 25 publications
(32 reference statements)
3
51
0
2
Order By: Relevance
“…As to piscivores, the duration and magnitude of floods have a positive effect on the reproductive success of many prey species, increasing food availability for this group (Fernandes et al, 2009). The 2009-2010 pulse presented characteristics that favored juvenile recruitment in most species of the Middle Paraná River floodplain (Abrial et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to piscivores, the duration and magnitude of floods have a positive effect on the reproductive success of many prey species, increasing food availability for this group (Fernandes et al, 2009). The 2009-2010 pulse presented characteristics that favored juvenile recruitment in most species of the Middle Paraná River floodplain (Abrial et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Esteves, Aranha (1999) have suggested that variations in fish assemblages due to hydrology can explain quantitative and qualitative changes in the diet of different trophic groups (detritivores, herbivores, omnivores, piscivores, planctivores, invertivores and insectivores). For instance, in the case of piscivores, an increment of the duration and magnitude of floods produced a positive effect on the reproductive success of many prey species (Fernandes et al, 2009). However, detritivores, omnivores and herbivores may be adversely affected during flood periods due to transport processes, since flow velocity increases and protein-rich food resources are carried away (Bowen, 1987;Faria, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…mercury), alterations in the water level, damming of rivers, and deposits of sewage and solid waste (Harris et al, 2005(Harris et al, , 2006. Deforestation, expanding agriculture, illegal fishing and hunting, unplanned tourism, and pollution by pesticides have those whose food supply is based on organic material (Britski et al, 2007;Fernandes et al, 2009). Additionally, demographically healthy populations of many endangered species such as the Brazilian giant otter (Pteronura brasiliensis), the jaguar (Panthera onca) and the greater hyacinth macaw (Anodorhynchus hyacinthinus) are still viable in the Pantanal.…”
Section: Threatsmentioning
confidence: 99%
“…Even small power-plants, which may not form a reservoir, can change the discharge of nutrients and suspended matter and hence the cycling of nutrients in affected water bodies (Calheiros et al, 2009;Fernandes, 2010). Furthermore, the presence of the physical barrier in the form of a dam is known to prevent the movement of migratory fish species during the spawning season, affecting fish production in the medium and long term (Fernandes et al, 2009;Suzuki et al, 2009). All these changes and negative impacts on the water ecology of each sub-basin forming the Pantanal should be assessed simultaneously, in terms of the integrated area of the Upper Paraguay River Basin, prior to installing such projects (Calheiros et al, 2009).…”
Section: River Flow Modification With Implantation Of Small Hydroelecmentioning
confidence: 99%
“…Authors as Suzuki et al (2009), for example, emphasize the importance of these two subsystems for spawning and early development of juveniles, especially of migratory species, as well as obtaining food and shelter. Moreover, these two subsystems are characterized by having greater richness and diversity of speciesin addition to high catch individuals in relation to the Paraná subsystem, indicating higher habitat quality (Fernandes et al, 2009).…”
Section: Methodsmentioning
confidence: 99%